Test of lepton universality in Υ(1S) decays at BABAR - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review letters, 2010)
The ratio Rτμ(Υ(1S))=ΓΥ(1S)→τ+τ−/ΓΥ(1S)→μ+μ− is measured using a sample of (121.8±1.2)×106Υ(3S) events recorded by the BABAR detector. This measurement is intended as a test of lepton universality and as a search for a possible light pseudoscalar Higgs boson. In the standard model (SM) this ratio is expected to be close to 1. Any significant deviations would violate lepton universality and could be introduced by the coupling to a light pseudoscalar Higgs boson. The analysis studies the decays Υ(3S)→Υ(1S)π+π−, Υ(1S)→l+l−, where l=μ, τ. The result, Rτμ(Υ(1S))=1.005±0.013(stat)±0.022(syst), shows no deviation from the expected SM value, while improving the precision with respect to previous measurements.
BABAR Collaboration: P. del Amo Sanchez, A. Adametz, J. Marks, S. Schenk, U. Uwer, T. Hartmann, T. Leddig, H. Schröder, R. Waldi [und viele weitere]
Gesehen am 23.08.2023